2012
DOI: 10.1080/1745039x.2012.710081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silver nanoparticles on growth performance, metabolism and microbial profile of broiler chickens

Abstract: This study evaluated the potential of silver nanoparticles (AgNano) as an antimicrobial growth-promoting supplement for broiler chickens. One hundred forty-four seven-day-old broiler chicks were distributed randomly to AgNano treatments at 0, 10 and 20 mg/kg (Control, Group AgNano10, and Group AgNano20, respectively) provided via the drinking water from day 7 to 36 post-hatching. Body weight and feed consumption were measured weekly. In addition, balance and respiration experiments were carried out to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
2
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 28 publications
8
62
2
5
Order By: Relevance
“…However, it can be speculated that the decrease in feed intake may be a response to the process of mechanical injection rather than silver nanoparticle exposure, because although conflicting results were obtained in quail 8 and weaned pigs, 21 no negative effect on feed intake has been reported as a result of silver nanoparticle supplementation in the feed or via the drinking water. The feed conversion ratio for the broilers did not differ between the treatment groups, which is accordance with the findings in quail 8 and broiler chickens 27 provided with silver nanoparticles via the drinking water, but not with data from weanling pigs supplemented with silver nanoparticle powder in the diet. 7 These conflicting results suggest that poultry species are either less sensitive to silver nanoparticle treatment than pigs, or that silver nanoparticles in powdered form provided via the feed is submit your manuscript | www.dovepress.com…”
Section: Growth Performancesupporting
confidence: 78%
See 1 more Smart Citation
“…However, it can be speculated that the decrease in feed intake may be a response to the process of mechanical injection rather than silver nanoparticle exposure, because although conflicting results were obtained in quail 8 and weaned pigs, 21 no negative effect on feed intake has been reported as a result of silver nanoparticle supplementation in the feed or via the drinking water. The feed conversion ratio for the broilers did not differ between the treatment groups, which is accordance with the findings in quail 8 and broiler chickens 27 provided with silver nanoparticles via the drinking water, but not with data from weanling pigs supplemented with silver nanoparticle powder in the diet. 7 These conflicting results suggest that poultry species are either less sensitive to silver nanoparticle treatment than pigs, or that silver nanoparticles in powdered form provided via the feed is submit your manuscript | www.dovepress.com…”
Section: Growth Performancesupporting
confidence: 78%
“…The concentrations of IgG and IgM in the plasma of broilers are not consistent with data from other researchers in which silver nanoparticles were only administered during the post-hatching period, 27 and it was demonstrated that silver nanoparticles reduced plasma IgG concentrations in broilers at a later age. Interestingly, this effect on IgG was eliminated when the broilers were injected with silver nanoparticles at the embryonic stage, suggesting that silver nanoparticles do not interact with the humoral immune system when introduced via in ovo injection.…”
Section: Microbial Profile and Immune Statuscontrasting
confidence: 39%
“…These fine particles have unique optical, electrical and thermal properties and are being used in wide range of products for antimicrobial coatings. These together gave SNPs a potential promising as potent constituents of pharmaceutical, medical and industrial products (Pineda et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, several studies have been designed to investigate the effects of nanosilver on vital and growth parameters of poultry such as performance, metabolism, gastrointestinal microflora, morphology of intestine, blood parameters, egg and meat qualities and development of chicken embryos. In these studies, it has been confirmed that defined concentrations of nanosilver was not harmful in the chickens in vivo (Sawosza et al, 2007;Mahmoud, 2012;Pineda et al, 2012a and2012b;Farzinpour and Karashi, 2013). However, in spite of the wide application of nanoparticles, there are few studies about the effect of these elements on animal and human health; and the mechanism of their toxicity is not completely clear.…”
Section: Introductionmentioning
confidence: 94%